Transformasi Pembelajaran PAI melalui Strategi Ekspositori dan Interactive Flat Panel Display (IFPD) - Windi Ariani; Wahyuni Ahadiyah (Pendidikan Agama Islam, 2025)
This research, entitled “Implementation of the Expository Strategy Assisted by Interactive Flat Panel Display (IFPD) Media in Islamic Religious Education (PAI) Learning for Grade VIII Students at SMP Al-Musaa’adah Tikung,” is motivated by the need of PAI teachers to improve the effectiveness of learning by combining the expository strategy with the use of IFPD media. The traditional lecture method was previously considered less effective in stimulating student interest, whereas the use of IFPD is believed to enhance the delivery of material in a more engaging and interactive way, particularly in the lesson